Coupled finite volume and finite element method analysis of a complex large-span roof structure - Szafran, Jacek; Juszczyk-Andraszyk, Klaudia; Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The main goal of this paper is to present coupled Computational Fluid Dynamics and structural analysis for the precise determination of wind impact on internal forces and deformations of structural elements of a long-span roof structure. The Finite Volume Method (FVM) serves for a solution of the fluid flow problem to model the air flow around the structure, whose results are applied in turn as the boundary tractions in the Finite Element Method problem structural solution for the linear elastostatics with small deformations.
Keywords: CFD simulation; finite volume method; Finite Element Method (FEM); wind engineering